Social Discontent and Voting Behaviour in South Africa’s 2024 General Elections: The Transition from One-party Dominance to a Multi-party Coalition - Ath`enkosi Mfusi Mbete; Collin Olebogeng Mongale; Victor Ojakorotu (E-Journal of Humanities, Arts and Social Sciences)
The main aim of this paper was to analyse South Africa’s transition from one-party dominance to a multi-party coalition government, with specific reference to the 2024 general elections in South Africa. Through the use of secondary data collection, the paper critically analysed the nexus between social discontent and voting behaviour in South Africa’s 2024 general elections. Using rational choice theory, the paper argued that voting behaviour in the 2024 elections was influenced by people’s choice to vote for a political party that promised to improve their welfare by addressing existing socio-economic challenges. The study found that the African National Congress (ANC), which has been a single dominant party in national government for 30 years, has failed to address pressing challenges that cause social discontent such as poor service delivery, poverty, unemployment, inequality, corruption, and the energy crisis. As a result, the party fell below the threshold to govern on its own, leading to the formation of a multi-party coalition government with former opposition parties named the Government of National Unity (GNU). The paper concluded that parties that form multi-party coalition government should prioritise people’s interests such as mitigating existing social discontents, because failure to do so shall influence voting behaviour in the upcoming election cycles, which might affect their electoral support as was the case with the ANC’s decline of support post-2024 general elections. This study anticipates making a valuable contribution to the existing body of knowledge by offering practical insights into the nexus between social discontent and voting behaviour in South Africa’s elections. In addition, the study provides recommendations on how the newly formed government of national unity can mitigate the existing social discount among electorates.